Synthesis, Characterization and Catechol-Based Bioinspired Adhesive Properties in Wet Medium of Poly(2-Hydroxyethyl Methacrylate-Co-Acrylamide) Hydrogels - Garcia-Herrera, C; Sanchez-Poblete, J; Inostroza-Inostroza, M; Martin-Trasancos, R; Martin-Trasancos, R (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Hydrogels consist of crosslinked hydrophilic polymers from which their mechanical properties can be modulated for a wide variety of applications. In the last decade, many catechol-based bioinspired adhesives have been developed following the strategy of incorporating catechol moieties into polymeric backbones. In this work, in order to further investigate the adhesive properties of hydrogels and their potential advantages, several hydrogels based on poly(2-hydroxyethyl methacrylate-co-acrylamide) with N′N-methylene-bisacrylamide (MBA), without/with L-3,4-dihydroxyphenylalanine (DOPA) as a catecholic crosslinker, were prepared via free radical copolymerization. 2-Hydroxyethyl methacrylate (HEMA) and acrylamide (AAm) were used as comonomers and MBA and DOPA both as crosslinking agents at 0.1, 0.3, and 0.5 mol.-%, respectively. The polymeric hydrogels were characterized by Fourier transform infrared spectroscopy (FT-IR), thermal analysis and swelling behavior analysis. Subsequently, the mechanical properties of hydrogels were determined. The elastic properties of the hydrogels were quantified using Young’s modulus (stress–strain curves). According to the results herein, the hydrogel with a feed monomer ratio of 1:1 at 0.3 mol.-% of MBA and DOPA displayed the highest rigidity and higher failure shear stress (greater adhesive properties). In addition, the fracture lap shear strength of the biomimetic polymeric hydrogel was eight times higher than the initial one (only containing MBA); however at 0.5 mol.-% MBA/DOPA, it was only two times higher. It is understood that when two polymer surfaces are brought into close contact, physical self-bonding (Van der Waals forces) at the interface may occur in an –OH interaction with wet contacting surfaces. The hydrogels with DOPA provided an enhancement in the flexibility compared to unmodified hydrogels, alongside reduced swelling behavior on the biomimetic hydrogels. This approach expands the possible applications of hydrogels as adhesive materials, in wet conditions, within scaffolds that are commonly used as biomaterials in cartilage tissue engineering. © 2024 by the authors.